Species identification, phylogenetic analysis and detection of herbicide-resistant biotypes of Amaranthus based on ALS and ITS - Han Xu (Nature Portfolio, 2020)
Abstract The taxonomically challenging genus Amaranthus (Family Amaranthaceae) includes important agricultural weed species that are being spread globally as grain contaminants. We hypothesized that the ALS gene will help resolve these taxonomic challenges and identify potentially harmful resistant biotypes. We obtained 153 samples representing 26 species from three Amaranthus subgenera and included in that incorporated ITS, ALS (domains C, A and D) and ALS (domains B and E) sequences. Subgen. Albersia was well supported, but subgen. Amaranthus and subgen. Acnida were not. Amaranthus tuberculatus, A. palmeri and A. spinosus all showed different genetic structuring. Unique SNPs in ALS offered reliable diagnostics for most of the sampled Amaranthus species. Resistant ALS alleles were detected in sixteen A. tuberculatus samples (55.2%), eight A. palmeri (27.6%) and one A. arenicola (100%). These involved Ala122Asn, Pro197Ser/Thr/Ile, Trp574Leu, and Ser653Thr/Asn/Lys substitutions, with Ala122Asn, Pro197Thr/Ile and Ser653Lys being reported in Amaranthus for the first time. Moreover, different resistant mutations were present in different A. tuberculatus populations. In conclusion, the ALS gene is important for species identification, investigating population genetic diversity and understanding resistant evolution within the genus Amaranthus.